Factors Influencing Financial Distress : Evidence from Indonesia Consumer Cyclical Companies - Melina Putri Rusmawati; Lenni Yovita; Vicky Oktavia; Suhita Whini Setyahuni (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research investigates the key factors influencing companies registered on the Indonesia Stock Exchange (IDX) that is experiencing financial distress between the years 2021 to 2023. In this study, 353 data points were selected from the target population using purposive sampling. Three key financial ratios were utilized as indicators of financial distress: Profitability can be measured by Return on Assets (ROA), while the Current Ratio (CR) is used to measure liquidity. Meanwhile, The Logarithm of Natural to Total Assets (LnTA) is a metric for evaluating a company’s size. Multiple regression analysis is performed utilizing SmartPLS 4.0 software to analyze the connection between these factors and the probability of experiencing financial distress. The findings indicate a significant negative association between liquidity (CR) and company size (LnTA) with financial distress. In contrast, profitability (ROA) demonstrates an insignificant negative correlation with financial distress. This study contributes to the literature by providing a comprehensive analysis of the factors influencing financial distress in Indonesia consumer cyclical companies employs signaling theory to interpret the relationships discovered.